Case report of spontaneous sino-cutaneous fstula in chronic rhinosinusitis - Wong, Song Yeu; Lim, Li Yun; Ramiza Ramza, Ramli; Tang, Ing Ping (Springer Nature, 2023)
Background Chronic rhinosinusitis (CRS) is a common disease characterized by infammation of the paranasal sinuses, with symptoms such as nasal blockage, facial pain, hyposmia, and headache. While these symptoms are often treated as a common cold, the disease can lead to serious complications if left untreated. We present an unusual case of CRS in which the patient presented to the ophthalmology department with persistent pus discharge from the left upper eyelid for 6 months, despite being treated with multiple courses of antibiotics and undergoing incision and drainage procedures. Case presentation A 69-year-old male patient presented with a 6-month history of persistent pus discharge from the left upper eyelid, despite being treated with multiple courses of oral antibiotics and three incision and drainage procedures. He also complained of yellowish nasal discharge and bilateral nasal blockage for the past year but did not seek medical attention for these symptoms. Physical examination revealed pus discharge from the left upper eyelid and widening of the nasomaxillary groove. Nasoendoscopic examination showed bilateral grade 3 nasal polyps with mucopus secretion. CT scan of the paranasal sinuses revealed that the odd presentation was due to the chronic inflammatory process in the paranasal sinuses, which had led to osteitis and hyperostosis. This patient underwent endoscopic sinus surgery (ESS) with left frontal trephination and fat obliteration of the left frontal sinus. The postoperative histopathological report confrmed the diagnosis of benign infammatory nasal polyp with acute on chronic infammation. The patient was asymptomatic at 3-month follow-up post-operation. Conclusion Our case report highlights the importance of considering CRS as a possible underlying cause of such unusual presentations, even when the symptoms may appear unrelated. Early diagnosis and treatment of CRS can prevent serious complications and improve patient outcomes. The infammatory process of CRS leading to osteitis and hyperostosis of the paranasal sinuses complicates the clinical presentation, distorts the usual anatomical structures, and may complicate the operation. CT scan of the paranasal sinus is highly recommended before any sinus surgery. At times, ESS may not be sufcient to eradicate fro